2012
DOI: 10.1371/journal.pbio.1001280
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial Activation and Repression by Seven Transcription Factors Specify Drosophila Odorant Receptor Expression

Abstract: A systematic analysis reveals a regulatory network controlling selective odorant receptor expression and neuronal diversity in Drosophila.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
138
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(146 citation statements)
references
References 39 publications
(41 reference statements)
6
138
0
Order By: Relevance
“…In Drosophila (unlike mammals) the expression of a given OR in a sensory neuron is not directly involved in glomerular targeting (62). Instead, upstream-acting transcription factors involved in neuronal differentiation separately specify both the downstream expression of a particular OR (63) and the axonal guidance of that neuron to its cognate glomerulus in the brain. In O. nubilalis, both strains possess the same cluster of ORs for pheromone detection.…”
Section: Discussionmentioning
confidence: 99%
“…In Drosophila (unlike mammals) the expression of a given OR in a sensory neuron is not directly involved in glomerular targeting (62). Instead, upstream-acting transcription factors involved in neuronal differentiation separately specify both the downstream expression of a particular OR (63) and the axonal guidance of that neuron to its cognate glomerulus in the brain. In O. nubilalis, both strains possess the same cluster of ORs for pheromone detection.…”
Section: Discussionmentioning
confidence: 99%
“…Given that a receptor gene is expressed in only one class of olfactory neurons (;20 cells) out of >100,000 neurons in the organism, it is very unlikely that each of ;50 ORN classes would possess a unique transcription factor code that is not recapitulated elsewhere in the nervous system. A recent study reported that seven transcription factors from different protein families could combinatorially regulate the expression of several olfactory receptors in the adult antenna (Jafari et al 2012). The MMB/dREAM complex appears to function in a different fashion, as it integrates the effect of transcriptional activators, repressors, and chromatin-modifying proteins in a single complex and acts as an adaptable molecular switch for Or expression.…”
Section: One Receptor Per Neuron: Combination Of Chromatin Accessibilmentioning
confidence: 99%
“…Moreover, negative-feedback regulation from the expressed rhodopsin can provide additional exclusion mechanisms to ensure one rhodopsin per photoreceptor ). In the Drosophila olfactory system, receptor gene expression is driven by combinatorial codes of cis-acting sites that recruit transcriptional activators and repressors without negative feedback being involved (Ray et al 2007Tichy et al 2008;Bai et al 2009;Bai and Carlson 2010;Miller and Carlson 2010;Jafari et al 2012). Based on these studies, transcription factors seem likely to act at two levels on olfactory receptor promoters: first to restrict expression in an organ-specific manner, and then within an organ to restrict expression to one class of neuron.…”
mentioning
confidence: 99%
“…The emerging evidence suggests that OR expression is controlled by dedicated combinations of positively and negatively acting TFs (Clyne et al, 1999a;Ray et al, 2007;Ray et al, 2008;Tichy et al, 2008;Bai et al, 2009;Bai and Carlson, 2010;Jafari et al, 2012;Song et al, 2012). A small number of TFs has been identified that is required to specify expression of OR genes, but how the expression or activity of the TFs themselves is regulated resulting in the broad distribution and intermingled pattern of sensillar subtypes is less well understood.…”
Section: Establishing and Maintaining Olfactory Receptor Expression Imentioning
confidence: 99%
“…In contrast to the repression of Rh5 by Rh6 in yR8 PRs, no evidence for one OR repressing an alternative OR gene has been found in Drosophila (Ray et al, 2007) (but see below for mouse). However, as in yR8 PRs, specification mechanisms do play a role in maintenance: at least some of the TFs involved in specification of OR gene expression are also continuously required for their maintenance (Jafari et al, 2012). Recently, evidence was found for epigenetic control of establishment and maintenance of OR expression in post-mitotic ORNs, which sense CO 2 (Sim et al, 2012).…”
Section: Primermentioning
confidence: 99%